Experimental and numerical analyses of manufacturing process of a composite square box part: Comparison between textile reinforcement forming and surface 3D weaving. (1st September 2015) - Wang, Peng; Legrand, Xavier; Boisse, Philippe; Hamila, Nahiène; Soulat, Damien
Abstract: Textile reinforcement forming is frequently used in aeronautic and automobile industries as a composite manufacturing process. The double-curved shape forming may be difficult to control and can lead to defects. Numerical simulation analysis can predict the suitable forming conditions and minimize the defects. Wrinkling as one of the most common flaws can be experienced easily during textile composite forming for certain specific shapes, for example the square box. In order to product a composite square box without wrinkles, a surface 3D weaving process has been developed to weave directly the shape of final part without the step of 2D preforming. In the surface 3D weaving the three directions are completely designed. The warp and weft yarns on all the surfaces of square box are absolutely under control and the final 3D ply has a homogeneous fibre volume fraction.